THE TOURIST INDUSTRY OF UKRAINE IN THE POST-WAR PERIOD: KEY DIRECTIONS OF RECOVERY AND FACTORS OF INFLUENCE IN THE EUROPEAN VECTOR OF DEVELOPMENT - Ольшанська, Олександра В.; Пузирьова, Поліна В.; Шевченко, Олег О. (Journal of Strategic Economic Research, 2024)
Through the process of researching and composing this article, it has been determined that the tourism industry of Ukraine before the start of the full-scale war was one of the competitive industries of the national economy, which brought the lion's share to the country's budget in the form of taxes and fees. Just as the tourism industry of Ukraine began to recover after the COVID-19-pandemic, it again suffered, without exaggeration, a big "blow" in the form of cutting off part of the territories and making it impossible for tourists to travel safely both within the country and beyond. It has been proven that the tourism industry in Ukraine has great potential for recovery, the country has a rich cultural heritage, natural beauty and historical sights that can attract the attention of not only domestic tourists but also enchant foreign visitors. It was determined that the Ukrainian tourism industry has great potential for recovery in the European context, as Ukraine is rich in cultural and natural treasures that can attract European tourists. It has been established that the restoration and development of infrastructure, improvement of service and marketing campaigns, ensuring safety and comfort for tourists form the foundations and deep interest in the Ukrainian tourism sphere. Flexible tourism approaches, such as environmentally friendly tourism and cultural exchange, can become key elements in the successful recovery of tourism in Ukraine in the European context. It has been determined that various measures can be considered to stimulate tourism, such as actions to promote tourist routes, partnerships with tour operators, infrastructure development, introduction of convenient services for tourists, and others. Several influencing factors regarding the revival of Ukrainian tourism through the prism of the European vector of development are proposed: political and economic stability; safety of tourists; reconstruction of infrastructure; active marketing and advertising; cultural heritage and natural resources; tourist policy and visa conditions; digital technologies in the field of tourism; economic condition of the country; tourist service. Among the general trends and possible directions for the restoration of the tourism industry in Ukraine in the post-war period, we identified the following: development of domestic tourism; cooperation with European partners; emphasis on the promotion of little-known tourist destinations; training of specialists in the field of tourism; accessibility of tourist trips to all travelers regardless of age, ability or interests.